Edge-Enhanced Disruptive Camouflage Impairs Shape Discrimination. (September 2019) - Sharman, Rebecca J.; Lovell, P. George
Disruptive colouration (DC) is a form of camouflage comprised of areas of pigmentation across a target's surface that form false edges, which are said to impede detection by disguising the outline of the target. In nature, many species with DC also exhibit edge enhancement (EE); light areas have lighter edges and dark areas have darker edges. EE DC has been shown to undermine not only localisation but also identification of targets, even when they are not hidden (Sharman, Moncrieff, & Lovell, 2018 ). We use a novel task, where participants judge which "snake" is more "wiggly, " to measure shape discrimination performance for three colourations (uniform, DC, and EE DC) and two backgrounds (leafy and uniform). We show that EE DC impairs shape discrimination even when targets are not hidden in a textured background. We suggest that this mechanism may contribute to misidentification of EE DC targets.